Experience of adoptive parenthood of a couple with biological children - Otuka, Livia Kuzumi; Scorsolini-Comin, Fabio; Santos, Manoel Antônio dos (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
This case study aimed at understanding the experience of adoptive parenthood in a couple with biological children. This case study aimed to understand how the conscious and unconscious fantasies are related to the experiences of adoptive parenthood. A couple with two biological daughters when they make the decision to adopt a child of two months involved in the study. The instrument used for data collection was the in-depth interview. The results show that the act of adoption took intense emotional significance for the couple, especially the learning of “being a mother” by adopting revealed to be a different experience as compared to the previous experience of motherhood based on consanguinity ties.